2018
DOI: 10.1172/jci94287
|View full text |Cite
|
Sign up to set email alerts
|

The BRG1/SOX9 axis is critical for acinar cell–derived pancreatic tumorigenesis

Abstract: Chromatin remodeler Brahma related gene 1 (BRG1) is silenced in approximately 10% of human pancreatic ductal adenocarcinomas (PDAs). We previously showed that BRG1 inhibits the formation of intraductal pancreatic mucinous neoplasm (IPMN) and that IPMN-derived PDA originated from ductal cells. However, the role of BRG1 in pancreatic intraepithelial neoplasia-derived (PanIN-derived) PDA that originated from acinar cells remains elusive. Here, we found that exclusive elimination of Brg1 in acinar cells of Ptf1a-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…Sox9 is a transcription factor that controls cell-fate decisions during embryonic development and homeostasis of a broad range of adult tissues [62][63][64] . Moreover, in cancer cells, SOX9 inhibits apoptosis and promotes proliferation, invasion, and metastasis [65][66][67] . Interestingly, two recent studies 44,45 have shown that transcriptional upregulation of Sox9 is an early cellular response to renal injury, and Sox9 is essential for repair and recovery post AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Sox9 is a transcription factor that controls cell-fate decisions during embryonic development and homeostasis of a broad range of adult tissues [62][63][64] . Moreover, in cancer cells, SOX9 inhibits apoptosis and promotes proliferation, invasion, and metastasis [65][66][67] . Interestingly, two recent studies 44,45 have shown that transcriptional upregulation of Sox9 is an early cellular response to renal injury, and Sox9 is essential for repair and recovery post AKI.…”
Section: Discussionmentioning
confidence: 99%
“…This is important as unique TE signatures in pre-malignant tissues that contribute to or are predictive of malignant transformation may be useful in the design of early diagnostic or therapeutic strategies (37). To this end, we determined the frequency and types of TEs expressed during pre-malignant (ADM) and malignant (PDAC) stages of pancreatic cancer utilizing an inducible model which restricts the oncogenic alleles Kras G12D and Trp53 R270H to pancreatic, acinar-specific expression through a tamoxifen-inducible Ptfa1-Cre promoter (38,39). Intraperitoneal administration of tamoxifen in 4-5 week old mice consistently results in a steady chronologic progression to PDAC that is equivalent to that observed in humans: ADM > pancreatic intraepithelial neoplasia (PanIN) > PDAC > liver and lung metastases (40).…”
Section: Transition From Adm To Pdac Is Characterized By Significant mentioning
confidence: 99%
“…Our previous work indicated ATF3 directly regulated expression of transcription factors involved in ADM [22]. IF for SOX9, which is required for ADM [36, 39], showed limited expression in saline-treated animals, localizing specifically to ductal epithelial cells. As previously reported, SOX9 expression was observed in acinar cells and ADM structures 1 and 7 days following rCIP in WT mice (Figure 3A, B).…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory showed ATF3 is required for ADM during acute injury [22] by activating Sox9 (Sry-related high-mobility group box 9) and repressing Mist1 , which maintains the mature acinar cell phenotype [35]. SOX9 and MIST1 are important regulators of ADM, required for [36] or limiting [37] PDAC progression through ADM/pancreatic intraepithelial neoplasia (PanIN) formation, respectively.…”
Section: Introductionmentioning
confidence: 99%